Periphery and Small Ones Matter Interplay of Policy and Social Capital - Azis, Iwan J. (Springer Nature, 2022)
This open access book analyzes the dualism and inequality insofar as how it is manifested in interregional disparity and small enterprises. Using the case of Indonesia, the author considers how the general direction of policy should be to mitigate the effects of agglomeration forces leading towards concentration, and exploit the same forces by encouraging small businesses to operate in a cluster for collective action. The book addresses these issues by focusing on the role of interactions between policies and institutions, of which social capital is an important part. This is an open access book.